Multiple small solutions for Kirchhoff equation with local sublinear nonlinearities. (September 2016) - Wang, Li-Li; Han, Zhi-Qing
Abstract: In this paper we discuss the following Kirchhoff equation in R N − ( a + b ∫ | ∇ u | 2 ) Δ u + V ( x ) u = f ( x, u ), where a, b > 0 are constants and N ≥ 3 . Without any growth condition for the nonlinear term f ( x, u ) on u at infinity, we obtain a sequence of solutions converging to zero in some Sobolev spaces.